Sol-gel synthesis and characterization of TiO2 powder - Kaygili, Omer; Bulut, Niyazi; Tatar, Cengiz; Ates, Tankut; İnce, Turan (Niyazi ÖZDEMİR, 2017)
In the present study, TiO2 powder having the tetragonal crystal without any impurity was easily synthesized by sol-gel method, and its characterization was done by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy. The crystallinity degree was found to be of 89.0%. A flaky morphology was observed.
Keywords: Engineering; Mühendislik